Migration triggers in a large herbivore: Galápagos giant tortoises navigating resource gradients on volcanoes. Issue 6 (18th April 2019) - Bastille‐Rousseau, Guillaume; Yackulic, Charles B.; Gibbs, James P.; Frair, Jacqueline L.; Cabrera, Freddy; Blake, Stephen
Abstract: To understand how migratory behavior evolved and to predict how migratory species will respond to global environmental change it is important to quantify the fitness consequences of intra‐ and inter‐individual variation in migratory behavior. Intra‐individual variation includes behavioral responses to changing environmental conditions and hence behavioral plasticity in the context of novel or variable conditions. Inter‐individual variation determines the degree of variation on which selection can act and the rate of evolutionary responses to changes in average and extreme environmental conditions. Here we focus on variation in the partial migratory behavior of giant Galápagos tortoises ( Chelonoidis spp.) and its energetic consequences. We evaluate the extent and mechanisms by which tortoises adjust migration timing in response to varying annual environmental conditions, and integrate movement data within a bioenergetic model of tortoise migration to quantify the fitness consequences of migration timing. We find strong inter‐individual variation in the timing of migration, which was not affected by environmental conditions prevailing at the time of migration but rather by average expectations estimated from multi‐annual averaged conditions. This variation is associated with an average annual loss in efficiency of ~15% relative to optimal timing based on year‐specific conditions. These results point towards a limited ability of tortoises to adjust the timing of their migrations based on prevailing (and, by extension, future) conditions, suggesting that the adaptability of tortoise migratory behavior to changing conditions is predicated more by past "normal" conditions than responses to prevailing, changing conditions. Our work offers insights into the level of environmental‐tuning in migratory behavior and a general framework for future research across taxa.